eCM 2011
DOI: 10.22203/ecm.v021a09
|View full text |Cite
|
Sign up to set email alerts
|

Cardiogel supports adhesion, proliferation and differentiation of stem cells with increased oxidative stress protection

Abstract: Cultured murine bone marrow derived mesenchymal stem cells (BMSC) when grown along with cardiogel derived from mouse cardiac fibroblast, exhibited increased cell proliferation and differentiation and enhanced survival under oxidative stress induced by the exposure of H 2 O 2 in vitro (similar to in vivo ischemia like condition). Adhesion of BMSC to the cardiogel occurred at a faster rate when compared to the cells grown on normal surface. BMSC attached to cardiogel showed an increased resistance to proteolytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Ex‐4 preconditioning protects MSCs against H 2 O 2 ‐induced apoptosis in a dose‐dependent manner, and pigment epithelium‐derived factor (PEDF) increases MSC survival rates in long‐term culture by attenuating p53 and p16 signalling . In addition, various types of extracellular matrix components including decellularized cell‐deposited extracellular matrix and cardiogel derived from cardiac fibroblast strongly promote the self‐renewal and differentiation of MSCs by up‐regulating the expression of intracellular antioxidative enzymes and maintaining low levels of ROS even under excessive H 2 O 2 conditions in vitro . In addition, Lai et al reconstructed a native extracellular matrix which is consisted of collagen, fibronectin, small leucine‐rich proteoglycans and major components of basement membrane to maintain the cell activities of MSCs via downregulation of ROS level in vitro.…”
Section: Strategies To Control Ros Levels For Msc Fates In Vitro and mentioning
confidence: 99%
“…Ex‐4 preconditioning protects MSCs against H 2 O 2 ‐induced apoptosis in a dose‐dependent manner, and pigment epithelium‐derived factor (PEDF) increases MSC survival rates in long‐term culture by attenuating p53 and p16 signalling . In addition, various types of extracellular matrix components including decellularized cell‐deposited extracellular matrix and cardiogel derived from cardiac fibroblast strongly promote the self‐renewal and differentiation of MSCs by up‐regulating the expression of intracellular antioxidative enzymes and maintaining low levels of ROS even under excessive H 2 O 2 conditions in vitro . In addition, Lai et al reconstructed a native extracellular matrix which is consisted of collagen, fibronectin, small leucine‐rich proteoglycans and major components of basement membrane to maintain the cell activities of MSCs via downregulation of ROS level in vitro.…”
Section: Strategies To Control Ros Levels For Msc Fates In Vitro and mentioning
confidence: 99%
“…The osteogenic cell (MC3T3-E1)-derived ECM, attached to the plates, promotes the osteogenic differentiation of embryonic stem cells seeded on the ECM (Evans et al 2010). It has been demonstrated that cardiac fibroblast-ECM supports early maturation of ES-derived cardiomyocytes in vitro (Baharvand et al 2005), and improves proliferate and cellular adhesion of BMSCs (Sreejit and Verma 2011). …”
Section: Introductionmentioning
confidence: 99%
“…6) Recently, the bioactivity of CF-derived ECM has been investigated in vitro. [11][12][13] However, the effects of CF-derived ECM on the metabolism, growth, and function of heart cells are not fully understood.…”
Section: Discussionmentioning
confidence: 99%